KOMUNIKASI INSTRUKTIF GURU DALAM MENINGKATKAN PRESTASI BELAJAR SISWA SMP INSAN NUR MUHAMMAD - Hidayat, Holid; Ratnamulyani, Ike Atikah; agustini, Agustini (JURNAL KOMUNIKATIO, 2019)
The implementation of instructive communication techniques to students at SMP Insan Nur Muhammad is done to improve student learning achievement. Learning achievement can be reached with support and motivation from school and home, good cooperation between the school and home becomes important in motivating students to have achievement. As Marwan who initially had difficulty in carrying out his duties as a BK teacher, giving guidance to students who were not disciplined to motivate student to study, but eventually Marwan succeeded in making students of SMP Insan Nur Muhammad outstanding and SMP Insan Nur Muhammad became one of the best schools in Tenjolaya District by getting several awards in various competitions among schools. The research aims to find out instructive communication in improving students learning achievement. The descriptive qualitative research method explains the phenomena accurately about the facts. Data collection techniques are done through observation, in-depth interviews, books, documentation, reports, and information. The results showed that instructional communication made by teachers with Fear Arousing, threats that given as punishment to students who are late, suspensions, parents’ summons, and repeat the same class to discipline and motivate students to become responsible, disciplined and outstanding students. This is also done by Red Hearing, the content of interests to win in a conflict such as direction, explanation, belief, attention, and understanding so that students become disciplined, follow the rules and become excellent students. The conclusion is BK teacher succeeded in providing motivation to students in their learning achievement. Keywords: Instructive Communication; Teacher; Learning Achievement; Students; School